1990
DOI: 10.1159/000117367
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Skin Potentials and Bulbocavernosus Reflex in Patients with Chronic Alcoholism and Impotence

Abstract: Fifteen chronic alcoholic male patients with impotence have been investigated with the electrophysiological method of sympathetic skin potentials recorded from the genital skin and with the electrically induced bulbocavernosus reflex. Both electrophysiological tests did not differ from those of normal controls. It was proposed that there is no obvious role of the peripheral neuropathic factors in the pathogenesis of impotence in chronic alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…22,23 Although a variety of neurophysiological techniques in diseases involving the pelvic floor are currently used, investigations of small afferent fibers are limited to sympathetic skin reflex by median nerve stimulation and perineal skin recording in traumatic spinal cord injury and sexual dysfunction in multiple sclerosis. [24][25][26] In addition, sympathetic skin reflex by penile stimulation and genital/limb recording has been used for the diagnosis of erectile dysfunctions in alcoholic/diabetic patients and amyloidotic polyneuropathy, [27][28][29] whereas nonconventional neurophysiological studies, such as LEPs, for assessing the involvement of small fibers in pelvic floor disorders are still lacking. 30 The aim of this study was to evaluate the feasibility and reproducibility of LEPs to pudendal area stimulation in healthy subjects and to compare LEPs with hand and foot stimulation.…”
mentioning
confidence: 99%
“…22,23 Although a variety of neurophysiological techniques in diseases involving the pelvic floor are currently used, investigations of small afferent fibers are limited to sympathetic skin reflex by median nerve stimulation and perineal skin recording in traumatic spinal cord injury and sexual dysfunction in multiple sclerosis. [24][25][26] In addition, sympathetic skin reflex by penile stimulation and genital/limb recording has been used for the diagnosis of erectile dysfunctions in alcoholic/diabetic patients and amyloidotic polyneuropathy, [27][28][29] whereas nonconventional neurophysiological studies, such as LEPs, for assessing the involvement of small fibers in pelvic floor disorders are still lacking. 30 The aim of this study was to evaluate the feasibility and reproducibility of LEPs to pudendal area stimulation in healthy subjects and to compare LEPs with hand and foot stimulation.…”
mentioning
confidence: 99%
“…Frequent alcohol misuse is also a risk factor for urinary tract infection [79] and hypogonadism [60]. Approximately 50% of male chronic alcohol misusers have either hypogonadism with reduced semen quality and quantity with (in some) abnormal spermatozoa [80,81]. Impotence also arises (Table II).…”
Section: Genitourinary and Reproductive Disorders Due To Alcohol Misusementioning
confidence: 99%
“…Unfortunately therefore, the test cannot be considered to be sufficiently discriminating to be used as a reliable clinical test. A study which evaluated the value of the SSR recorded from the limbs and genital region in 42 patients with urinary and/or sexual complaints found that abnormalities of the SSR could be detected in those patients with polyneuropathy [ 89]. More had an abnormality of the SSR recorded from the lower limbs than from the genital region, but there were two patients who had normal neurophysiological investigations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In men with chronic alcoholism and ED, no difference could be detected in the SSR recorded from the genital region between a patient group and controls. From this it was concluded that the problem was not due to an autonomic peripheral neuropathy [ 89].…”
Section: Introductionmentioning
confidence: 99%